Live fences, pastures and riparian forest: How agricultural lands contribute to bird diversity in northern Costa Rica - Maglianesi, María (2026)
Agricultural expansion is a major driver of biodiversity loss in tropical regions, yet humandominated landscapes also hold potential for biodiversity conservation when managed as multifunctional mosaics that retain patches of native vegetation. We assessed how natural and semi-natural habitats contribute to avian diversity in a tropical livestock farm in northern Costa Rica. Over one year, bird assemblages were sampled across three habitat types (live fences, pastures and riparian forest) at La Balsa farm. Using point counts surveyed every month during the year, we recorded 165 bird species, including 20 migratory and 6 species of global conservation concern, and 4 regionally endemic species. Species richness and overall abundance were lower in the riparian forest compared to live fences and pastures, and bird assemblage composition differed markedly among habitats, with the community in the riparian forest exhibiting a distinct assemblage structure. These results indicate that though the riparian forest hosts fewer species and individuals, it harbors a characteristic bird assemblage, highlighting its irreplaceable ecological role in providing habitat to forest-dependent species. Overall, the findings underscore that structurally diverse agricultural mosaics can sustain remarkably high bird diversity when complemented by habitats including native vegetation.